The use of medicines in treating lipid disorders at Thuan Thao General Clinic in the first 6 months of 2024 - Trần , Huyền Trân; Nguyen , Thị Ánh Tuyết; Le , Văn Út; Trinh , Thị Nhung (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Dyslipidemia is one of the leading risks leading to dangerous cardiovascular events. Timely detection and effective treatment will limit the risk of death caused by cardiovascular diseases. Cross-sectional descriptive research method was conducted on 426 prescriptions of patients with lipid disorders at Thuan Thao General Clinic from January 1, 2024 to June 30, 2024. The majority of patients are male with a rate of 54,23%. The age group mainly from 55 - 69 years old accounts for the highest proportion with 67,37%. Triglyceride, total cholesterol and LDL-C indexes were mostly at borderline high levels with 81,92%; 80,05% and 84,04% respectively, HDL-C indexes were all at normal levels at all patients in the study sample. Most clinics use a treatment regimen of Statin monotherapy, accounting for 96,00%; Atorvastatin is used the most with 92,25% mainly at medium intensity, reaching 56,10%. Rosuvastatin only accounts for 3,76%. Fenofibrate was used at a rate of 2,58%, and Statin + fibrate regimen at 1,41%. Dyslipidemia drugs are usually combined with drugs to treat hypertension and diabetes. Patients are prescribed groups of drugs that are on the Ministry of Health’s list of recommended treatments for lipid disorders